Impact of ChatGPT in Higher Education Learning - Jemmy, Jemmy; Aina, Mia; Wahdah, Wahdah; Joshua, Wang; Sabri, Sabri (Journal International of Lingua and Technology, 2024)
The existence of technology in the world of education is a very important need. As time goes by, technology is developing rapidly along with the intelligence and creativity of the generation that will be the successor of the nation in the future. Therefore, students must also be able to develop technology in learning such as ChatGPT. The purpose of this study was to determine the impact of ChatGPT in learning in college as a medium that can help lectures. The method used in this research is quantitative method, data obtained through online questionnaire distribution. The results found that there are various impacts such as ChatGPT can make it easier for students to do some of their assignments, however, socially the interaction and communication between students and lecturers will be reduced, because in the world of education what is needed is not only grades, but also the process that makes it clear that ChatGPT can be beneficial because it can help with assignments, but on the other hand, there is a lack of communication between lecturers and students. The limitation of this study is that researchers only conducted research on some students in higher education so that the data obtained is less relevant. Penliti hopes that future researchers can conduct more in-depth research. This research also recommends ChatGPT in college.